Optic nerve decompression in Craniofacial fibrous dysplasia involving optic canal: An experience at AIIMS, New Delhi - Ahmed, Bashir; Thakkar, Alok; Irfan, SM Nurul (Bangladesh Journal of Otorhinolaryngology, 2019)
Background: Gradual progression of craniofacial fibrous dysplasia frequently involves sphenoid and ethmoid bone results encasement of optic canal which leads to visual impairment to complete blindness Methods: Retrospective study was carried out at All India Institute of Medical Sciences on hospital records of 16 cases of craniofacial fibrous dysplasia operated for optic canal involvement with or without visual impairment with an objective to discuss about the indications, suitable timing and outcome of optic nerve decompression in cases of optic canal involvement. Results: Out of 16 cases, 56.25% were female with mean age 13.06 years. 15 patients had Idiopathic Fibrous dysplasia and 01 had Cranio-metaphyseal dysplasia. 62.5% were polyostotic and 37.5% were monostotic with 62.5% of optic neuropathy. Bilateral lesion occurred in 03 patients. Optic nerve decompression was done for curative treatment in 62.5% and for prophylactic in 37.5% cases. Post-operative visual improvement occurred in 90% patients and in no patient vision was deteriorated. Conclusion: Prophylactic decompression can be carried out in expert hand for involvement of optic canal in craniofacial fibrous dysplasia for prevention of future visual impairment Bangladesh J of Otorhinolaryngology; October 2018; 24(2): 94-104